Comparison of left ventricular myocardial function before and after sports season in professional male adolescent football players - Dorobantu, D. M.; Wadey, C.; Ryding, D.; McNally, S.; Perry, D.; Stuart, A. G.; Pieles, G. E.; Williams, C. A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Professional athletes undergo intense and rigorous training regimens during sporting seasons, and whether there are any post-season changes in cardiac function, beneficial or detrimental to performance e.g., cardiac fatigue, is not well known. The aim of this preliminary study was to compare left ventricular (LV) myocardial function before and after a competitive season in a group of adolescent elite football players, using state-of-the-art echocardiographic exercise testing.